Philosophes taoïstes : Lao-tseu, Tchouang-tseu, Lie-tseu - Lao-tseu; Tchouang-tseu; Lie-tseu; Étiemble, René; Liou, Kia-hway.; Grynpas, Benedykt; Demiéville, Paul.; Kaltenmark, Max (Paris Gallimard, 1980)
Ce vol. contient: Tao-to king/ Lao-tseu; L'oeuvre complète/ Tchouang-tseu; Le vrai classique du vide parfait/ Lie-tseu
Répertoire (gloss.)